Prevalence, comorbidities and mortality of generalized pustular psoriasis: A literature review. (3rd December 2022) - Prinz, Jörg C.; Choon, Siew Eng; Griffiths, Christopher E. M.; Merola, Joseph F.; Morita, Akimichi; Ashcroft, Darren M.; Viguier, Manuelle
Abstract: Generalized pustular psoriasis (GPP) is a rare auto‐inflammatory skin disease characterised by acute episodes of sterile pustule formation. Diagnosis and treatment of the disease have historically been complicated by a lack of awareness, and no consistent global definition or clinical coding standards. Now acknowledged as a distinct clinical entity with a recognised genetic component, GPP can take a serious and life‐threatening course due to systemic inflammatory complications and its association with various comorbidities. As with other rare diseases, there are significant challenges to understanding the epidemiology of GPP, notably a small patient population, non‐standardised study methodologies and ethnic differences in its presentation. A clearer understanding of GPP is therefore required for clinicians to better manage patients with this rare condition. In this review article, we present an overview of the available data on GPP prevalence estimates in key demographics and report the frequency of genetic mutations associated with the disease. We detail the incidence of known comorbidities and summarise the data on mortality and assigned causes of death. Lastly, we discuss the various factors that impact the collection, interpretation and comparison of these data.